Identifying biomarkers of dementia prevalent among amnestic mild cognitively impaired ethnic female patients. Issue 1 (December 2016) - Grewal, Rinko; Haghighi, Mona; Huang, Shuai; Smith, Amanda; Cao, Chuanhai; Lin, Xiaoyang; Lee, Daniel; Teten, Nancy; Hill, Angela; Selenica, Maj-Linda
Abstract Background There is a need to investigate biomarkers that are indicative of the progression of dementia in ethnic patient populations. The disparity of information in these populations has been the focus of many clinical and academic centers, including ours, to contribute to a higher success rate in clinical trials. In this study, we have investigated plasma biomarkers in amnestic mild cognitively impaired (aMCI) female patient cohorts in the context of ethnicity and cognitive status. Method A panel of 12 biomarkers involved in the progression of brain pathology, inflammation, and cardiovascular disorders were investigated in female cohorts of African American, Hispanic, and White aMCI patients. Both biochemical and algorithmic analyses were applied to correlate biomarker levels measured during the early stages of the disease for each ethnicity. Results We report elevated plasma Aβ40, Aβ42, YKL-40, and cystatin C levels in the Hispanic cohort at early aMCI status. In addition, elevated plasma Aβ40 levels were associated with the aMCI status in both White and African American patient cohorts by the decision tree algorithm. Eotaxin-1 levels, as determined by the decision tree algorithm and biochemically measured total tau levels, were associated with the aMCI status in the African American cohort. Conclusions Overall, our data displayed novel differences in the plasma biomarkers of the aMCI female cohorts where the plasma levels of several biomarkers distinguished between each ethnicity at an early aMCI stage. Identification of these plasma biomarkers encourages new areas of investigation among aMCI ethnic populations, including larger patient cohorts and longitudinal study designs.